2017
DOI: 10.11648/j.jddmc.20170301.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physicochemical, Thermal, Structural, and Behavioral Properties of Magnesium Gluconate Treated with Energy of Consciousness (The Trivedi Effect<sup>®</sup>)

Abstract: Magnesium gluconate is a classical organometallic salt used for the prevention and treatment of magnesium deficiency diseases. The objective of the current research was to explore the influence of The Trivedi Effect ® -Energy of Consciousness Healing Treatment (Biofield Energy Healing Treatment) on magnesium gluconate for the change in the physicochemical, structural, thermal and behavioral properties using PXRD, PSD, FT-IR, UV-vis spectroscopy, TGA, and DSC analysis. Magnesium gluconate was divided into two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…The National Center of Complementary and Integrative Health (NCCIH) has been recognized and accepted Biofield Energy Healing as CAM health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, Tai Chi, Qi Gong, chiropractic/osteopathic manipulation, meditation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, relaxation techniques, hypnotherapy, healing touch, movement therapy, Pilates, Rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, Reiki, cranial sacral therapy and applied prayer (as is common in all religions, like Christianity, Hinduism, Buddhism and Judaism) [21]. The Trivedi Effect ® -Biofield Energy Consciousness Healing Treatment has astonishingly ability to transform the characteristic properties of several organic compounds [22][23][24][25], pharmaceuticals [26,27], nutraceuticals [28], metals and ceramic [29,30], culture medium [31,32] and improve the overall productivity of agricultural crops [33,34], skin health [35,36], modulation in the efficacy of various living cells [37][38][39], and alteration of the isotopic abundance ratio in the organic compounds [40][41][42][43]. Thus, this study was designed to analyses the impact of Biofield Energy Treatment (The Trivedi Effect ® ) on the physicochemical, thermal, and spectroscopic properties of copper chloride by using various analytical techniques such as, powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), UV-visible, and FT-IR spectroscopy.…”
Section: The Use Of Complementary Therapies Such As Biofield Energymentioning
confidence: 99%
“…The National Center of Complementary and Integrative Health (NCCIH) has been recognized and accepted Biofield Energy Healing as CAM health care approach in addition to other therapies, medicines and practices such as natural products, deep breathing, yoga, Tai Chi, Qi Gong, chiropractic/osteopathic manipulation, meditation, massage, special diets, homeopathy, progressive relaxation, guided imagery, acupressure, acupuncture, relaxation techniques, hypnotherapy, healing touch, movement therapy, Pilates, Rolfing structural integration, mindfulness, Ayurvedic medicine, traditional Chinese herbs and medicines, naturopathy, essential oils, aromatherapy, Reiki, cranial sacral therapy and applied prayer (as is common in all religions, like Christianity, Hinduism, Buddhism and Judaism) [21]. The Trivedi Effect ® -Biofield Energy Consciousness Healing Treatment has astonishingly ability to transform the characteristic properties of several organic compounds [22][23][24][25], pharmaceuticals [26,27], nutraceuticals [28], metals and ceramic [29,30], culture medium [31,32] and improve the overall productivity of agricultural crops [33,34], skin health [35,36], modulation in the efficacy of various living cells [37][38][39], and alteration of the isotopic abundance ratio in the organic compounds [40][41][42][43]. Thus, this study was designed to analyses the impact of Biofield Energy Treatment (The Trivedi Effect ® ) on the physicochemical, thermal, and spectroscopic properties of copper chloride by using various analytical techniques such as, powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), UV-visible, and FT-IR spectroscopy.…”
Section: The Use Of Complementary Therapies Such As Biofield Energymentioning
confidence: 99%
“…The powder X-ray diffraction (PXRD) analysis of iron sulphate was performed with the help of PANalytical X'Pert3 Pro [34,35,38]. The average crystallites size was calculated using the Scherrer's formula (1) G = kλ/βcosθ (1) Where G is the crystallite size in nm, λ is the radiation wavelength, k is the equipment constant, β is the full-width half maximum, and θ is the Bragg angle [38,39]. The particle size distribution (PSD) analysis of iron sulphate powder sample was performed with the help of Malvern Mastersizer 3000, UK instrument using the wet method.…”
Section: Characterizationmentioning
confidence: 99%
“…Similarly, the differential scanning calorimetry (DSC) analysis of iron sulphate was performed with the help of DSC Q200, TA instruments. The thermal gravimetric analysis (TGA) thermograms of iron sulphate were obtained with the help of TGA Q50 TA instruments [34,35,38]. The % change in crystallite size, peak intensity, particle size, surface area, melting point, latent heat, weight loss and the maximum thermal degradation temperature of the Biofield Energy Treated iron sulphate was calculated compared to the control sample using the following equation 2:…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Various scientific studies reported that Biofield Energy Healing have significant outcomes which showed more effective alternative, respective to other approaches [20]. Treatment have been reported scientifically to transform the characteristic properties of living organism and non-living substances in the field of microbiology [22][23][24], cancer cells [25], agricultural crops [26][27][28], pharmaceutical medium [29,30], material science [31,32], pharmaceutical compounds [33,34], nutraceutical [35][36][37], and organic compounds [38][39][40].…”
Section: Introductionmentioning
confidence: 99%